PKCδ/MAPKs and NF-κB Pathways are Involved in the Regulation of Ingenane-Type Diterpenoids from Euphorbia neriifolia on Macrophage Function - Jiang M; Xue Y; Li J; Rao K; Yan S; Li H; Chen X; Li R; Liu D (Dove Medical Press, 2021)
Mingyan Jiang,* Yong Xue,* Jianchun Li, Kairui Rao, Shili Yan, Hongmei Li, Xuanqin Chen, Rongtao Li, Dan Liu Center for Pharmaceutical Sciences and Engineering, Faculty of Life Science and Technology, Kunming University of Science and Technology, Kunming, Yunnan, People's Republic of China*These authors contributed equally to this workCorrespondence: Rongtao Li; Dan Liu Tel +86 871 65920657Email rongtaolikm@163.com ; liudankm512@163.comPurpose: Euphorbia neriifolia Linn. has important medicinal value in the treatment of ulcers, tumors, inflammation, chronic respiratory troubles, and so on. Although many ingredients with anti-inflammatory activity have been discovered and isolated from the Euphorbia neriifolia, the current research still cannot explain its multivariate effects on the immune response. This article aims to introduce two Ingenane-type diterpenoids from Euphorbia neriifolia with macrophage regulatory effects and to investigate the mechanism of their action.Methods: The stem bark of E. neriifolia was extracted with various separation methods to obtain ingenane-type diterpenoids. The RAW264.7 cells were treated with lipopolysaccharide (LPS, 1 μg/mL) to establish an inflammatory cell model. The cell viability was detected by MTT assay. The secretion of PGE2, TNF-α, IL-1β, and IL-6 was tested with ELISA. The levels of iNOS, COX-2, IκBα, JNK, ERK, p38, p-IκBα, p-JNK, p-ERK, and p-p38 in cells were detected by Western blotting. The translocation of nuclear factor-kappa B (NF-κB)/p65 subunit were evaluated by Immunofluorescence staining.Results: Ingenane-type diterpenoids, eurifoloid A (Euri A) and a new compound euphorneroid E (Euph E), were isolated from the EtOAc fraction of E. neriifolia stem bark extracts. Euph E and Euri A exhibited significant inhibition on the levels of pro-inflammatory mediators NO, IL-1β, IL-6, and iNOS on LPS-induced macrophage RAW264.7. Cellular signaling pathway studies showed that they prevented the degradation of IκBα and the translocation of NF-κB/p65 subunit. Furthermore, the production of PGE2, TNFα, and COX-2 was dramatically increased under the influence of the compounds, which were closely related to the phosphorylation of protein kinase C δ (PKCδ) and activation of mitogen-activated protein kinase (MAPKs) signaling pathway.Conclusion: These results demonstrated that Euph E and Euri A exhibited multidirectional regulation on cytokines and immune function of macrophages, in addition to a good anti-inflammatory activity, and which was closely related to the regulation of PKCδ/MAPKs and NF-κB signal pathways.Graphical abstract: Keywords: euphorneroid E, eurifoloid A, ingenane-type diterpenoids, Euphorbia neriifolia, M-macrophage, immunoregulation